Glioblastoma 2017
DOI: 10.15586/codon.glioblastoma.2017.ch9
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging in Glioblastoma: Use in Clinical Practice

Abstract: Positron emission tomography (PET) is a nuclear medicine imaging method with increasing relevance for the diagnosis, prognostication, and monitoring of glioblastomas. PET provides additional insight beyond magnetic resonance imaging (MRI) into the biology of gliomas, which can be used for noninvasive grading, differential diagnosis, delineation of tumor extent, planning of surgery, and radiotherapy and post-treatment monitoring. In clinical practice, two classes of radiotracers have been used predominantly for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 110 publications
0
26
0
Order By: Relevance
“…With applying these procedures, [ 18 F]FDG has shown acceptable sensitivity for the identification of anaplastic abnormalities in patients with low-grade glioma (LGG), high-grade glioma (HGG; Figure 1a [24]), CNS lymphoma, brain metastases, and meningioma [25][26][27]. Moreover, higher [ 18 F]FDG uptake has shown a positive correlation with higher histologic grade and worse prognosis [26,28], making [ 18 F]FDG PET a suitable tool for the prediction of progression-free survival (PFS) and overall survival (OS) [29]. [ 18 F]FDG PET has shown not to be suited for radiation treatment planning, since the region of increased uptake generally covers a smaller volume than what was defined as malignant on T1-weighted gadolinium and T2-weighted MR-images [30].…”
Section: Diagnostic Imaging Of Abnormal Metabolic Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…With applying these procedures, [ 18 F]FDG has shown acceptable sensitivity for the identification of anaplastic abnormalities in patients with low-grade glioma (LGG), high-grade glioma (HGG; Figure 1a [24]), CNS lymphoma, brain metastases, and meningioma [25][26][27]. Moreover, higher [ 18 F]FDG uptake has shown a positive correlation with higher histologic grade and worse prognosis [26,28], making [ 18 F]FDG PET a suitable tool for the prediction of progression-free survival (PFS) and overall survival (OS) [29]. [ 18 F]FDG PET has shown not to be suited for radiation treatment planning, since the region of increased uptake generally covers a smaller volume than what was defined as malignant on T1-weighted gadolinium and T2-weighted MR-images [30].…”
Section: Diagnostic Imaging Of Abnormal Metabolic Processesmentioning
confidence: 99%
“…Subsequent studies showed a correlation between both uptake intensity and uptake volume and survival after radiotherapy, where higher intensity and larger volumes corresponded with worse survival [62][63][64] (Figure 1e) [69,76]. Most studies found [ 18 F]FLT uptake only in areas of contrast enhancement on MRI, suggesting a dependency on BBB disruption [21,29]. One study by Jacobs et al, on the other hand, showed an uptake of [ 18 F]FLT also in non-enhancing tumor areas and in LGG.…”
Section: Diagnostic Imaging Of Abnormal Metabolic Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Positron emission tomography (PET scan) is now standardly used to highlight the tumor sites thanks to this specific signature. 22,23 The increased glycolytic metabolism is related to hypoxia: as the tumor grow the increased cell population increases oxygen consumption and contribute to the local vascular disruption that together result in a local deficit of oxygen. To survive, the cells switch their metabolism to glycolysis.…”
Section: Extracellular Phmentioning
confidence: 99%
“…Another important technique for therapeutic follow up analysis in glioma models is the PET that display functional and biological information, such as metastatic lesion and tumor level staging of III and IV [49,[58][59][60][61][62]. PET has high diagnostic, prognostic, and therapeutic evaluation value when integrating with CT or MRI informations [61,62] for drug metabolism and PET radiotracers as 18 F-2-fluoro-2-deoxy-D-glucose ( 18 F-FDG) which evaluates glucose metabolism. High-grade gliomas, such as GBM, are known to consume high glucose levels.…”
Section: Introductionmentioning
confidence: 99%